Study of the utilization of main crop straw resources in Southern China and its potential as a replacement for chemical fertilizers - Mu, Guiting; Xu, Lifu; Zhang, Jiachun (Frontiers in Plant Science, 2024)
Although straw returning to the field (SRTTF) is conducive to promoting sustainable agricultural production and protecting the environment, straw resources are still wasted due to the lack of suitable straw-returning technology in southern China. Based on the statistical yearbook and a large number of studies, different methods were used to calculate the total straw resources and SRTTF potential, and differences in these methods were compared. The results indicate that the total amount of straw resources in southern China in 2021 was 3.35×108 t. The nutrient content of K2O in the straw accounted for the highest proportion of total nutrient resources (63.66%), followed by N (26.88%) and P2O5 (9.46%). In theory, total SRTTF could replace almost all K2O and part of N and P2O5, indicating that the nutrient substitution potential of SRTTF was high. It is suggested that the SRTTF method be adopted in the middle and lower reaches of the Yangtze River, which mainly uses direct returning (DR) supplemented by indirect returning (IDR). In southeast China, straw returning is carried out by the combination of IDR and IR. In southwest China, straw returning is mainly carried out by IR and supplemented by MDR. This study will provide theoretical support for the government to formulate straw-returning policy.